Accurate and sensitive determination of cobalt in urine samples using deep eutectic solvent-assisted magnetic colloidal gel-based dispersive solid phase extraction prior to slotted quartz tube equipped flame atomic absorption spectrometry - Borahan, Tulay; Zaman, Buse Tugba; Ozzeybek, Gozde; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2021)
In this study, a colloidal gel of magnetic Fe3O4 nanoparticles was used in the development of a simple and accurate dispersive solid phase extraction method for the extraction/preconcentration of trace levels of cobalt ions in urine samples. The eluted cobalt ions were determined by slotted quartz tube-flame atomic absorption spectrophotometry (SQT-FAAS). The effects of the type and volume of buffer solution, volume of magnetic colloidal gel, type and period of mixing, concentration and volume of the eluent were investigated and optimized to obtain the best experimental outputs. Under the optimum conditions, the limits of detection and quantification were found as 4.6 and 15 ng mL(-1), respectively. The developed method provided a 61.5 folds enhancement in the detection power of the flame atomic absorption spectrophotometry. Method validation was performed by spiking experiments using matrix matching method. The percent recoveries were found to be close to 100% for the spiked samples, which validate the accuracy and the applicability of the developed method to the urine samples.
Keywords: Cobalt; Fe3O4 nanoparticles; Colloidal gel; Deep eutectic solvent; Dispersive solid phase extraction; Urine; Chemistry